2011
DOI: 10.1245/s10434-011-1944-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RhoGDI2 Correlates with Tumor Progression and Poor Prognosis in Colorectal Carcinoma

Abstract: Over-expression of RhoGDI2 is associated with poor overall survival in CRC patients, especially those presenting in early-stage. RhoGDI2 contributes to cell proliferation, motility, and invasion of CRC, at least in part, by activating the PI3K/Akt pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…However, increasing evidence shows that D4-GDI is also expressed in nonhematopoietic neoplasms [5,9,11,20,27,37,38]. The elevated D4-GDI expression has been associated with tumor growth and malignant progression of ovarian [37], lung [27], gastric [5] and colorectal cancers [20]. In line with these observations, we have previously shown that D4-GDI is highly expressed in a panel of 8 breast cancer cell lines but not in normal mammary epithelial cells [45].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, increasing evidence shows that D4-GDI is also expressed in nonhematopoietic neoplasms [5,9,11,20,27,37,38]. The elevated D4-GDI expression has been associated with tumor growth and malignant progression of ovarian [37], lung [27], gastric [5] and colorectal cancers [20]. In line with these observations, we have previously shown that D4-GDI is highly expressed in a panel of 8 breast cancer cell lines but not in normal mammary epithelial cells [45].…”
Section: Discussionmentioning
confidence: 56%
“…In support of this notion, depletion of D4-GDI in MDA-MB-231 breast cancer cells suppressed invasive phenotypes both in vitro and in animal models [44,45]. Likewise, overexpression of D4-GDI in colorectal cancer cells promoted cell proliferation and in vitro motility and invasion [20]. On the other hand, our results show that the majority (78%) of malignant breast cancer and all metastatic lymph nodes samples had little or undetectable D4-GDI immunoreactivity which is in agreement with reports by others [12,25,33].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…By contrast, another study suggested that the cleavage of RhoGDI2 by caspase-3 is not a functionally irrelevant effect of caspase activation during apoptosis but rather expedites the progression of the apoptotic process (23). Unlike bladder cancer and lymphoma cells, RhoGDI2 was reported as an oncogene in breast, colon and gastric cancer cells (9,10,24). A Korean group reported that RhoGDI2 confers resistance to cisplatin-induced apoptosis in gastric cancer cells by upregulating Bcl-2 expression and activating PLCγ (19,25).…”
Section: Discussionmentioning
confidence: 99%
“…The other 14, most of which are already known to be involved in cancer (TGFB2, NTF3 (29), UACA (30), SFRP4 (31), and ULBP2 (32), were overexpressed. Another gene like ARHGDIB has been associated with prognosis (33,34) and cisplatin resistance (35). Selected genes were validated at the protein level ( Supplementary Fig.…”
Section: Refining the Fpg Signature: Developing A Classifiermentioning
confidence: 99%